The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3126/saarctb.v16i1.23244
|View full text |Cite
|
Sign up to set email alerts
|

Study on Culture Positivity among Sputum Smear Negative Tuberculosis Suspects attending the National Tuberculosis Centre, Nepal

Abstract: Background: Globally, more than half of all TB cases are not detected. If they are not diagnosed and get treatment infection transmission may continue and patients suffer and may eventually die. Pulmonary TB either smear positive or negative is normally diagnosed by Ziehl-Neelsen stained sputum smear examination microscopy. Since the culture is the gold standard, evaluation of smear negative TB cases by this method is likely to detect more cases. Objectives: The objective of this study is to find out cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…When assessing 90 studies that adopted the most inclusive (‘universal’) testing approach, the studies were very heterogeneous, and the overall proportion of DR-TB cases detected ranged from 0% in two studies conducted in Malawi and Nepal, to 52.8% in a study from India where presumptive TB cases with and without risk factors for DR-TB were involved. 39 44 106 When assessed by different burden of DR-TB as reported in the 2015 WHO list, 62 studies reported on universal DST in high MDR-TB burden countries. The yield of resistant cases identified across these studies also varied widely, ranging from 0% to 86%.…”
Section: Resultsmentioning
confidence: 99%
“…When assessing 90 studies that adopted the most inclusive (‘universal’) testing approach, the studies were very heterogeneous, and the overall proportion of DR-TB cases detected ranged from 0% in two studies conducted in Malawi and Nepal, to 52.8% in a study from India where presumptive TB cases with and without risk factors for DR-TB were involved. 39 44 106 When assessed by different burden of DR-TB as reported in the 2015 WHO list, 62 studies reported on universal DST in high MDR-TB burden countries. The yield of resistant cases identified across these studies also varied widely, ranging from 0% to 86%.…”
Section: Resultsmentioning
confidence: 99%